The Impact of Ly49-NK Cell-Dependent Recognition of MCMV Infection on Innate and Adaptive Immune Responses. (22nd May 2011) - Pyzik, Michal; Gendron-Pontbriand, Eve-Marie; Vidal, Silvia M.
Abstract : Clinical and experimental data indicate that a subset of innate lymphocytes, natural killer (NK) cells, plays a crucial role in the response against herpesviruses, especially cytomegaloviruses (CMV). Indeed, in mice, NK cells, due to the expression of germline encoded Ly49 receptors, possess multiple mechanisms to recognize CMV infection. Classically, this results in NK cell activation and the destruction of the infected cells. More recently, however, this unique host-pathogen interaction has permitted the discovery of novel aspects of NK cell biology, implicating them in the regulation of adaptive immune responses as well as in the development of immunological memory. Here, we will concisely review the newly acquired evidence pertaining to NK cell Ly49-dependent recognition of MCMV-infected cell and the ensuing NK cell regulatory responses.